Risk assessment and the effects of overhead work - an automotive industry example - Elliott, Andrew Brent (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2008)
The focus of this investigation was an analysis of the work demands being placed on South African automotive industry workers as there is a recognised problem with regard to the prevalence of musculoskeletal disorders (MSDs). Preliminary work was conducted to highlight the dominant risks and areas which elicited higher numbers of MSDs within the chosen automotive plant. An area of concern was highlighted through medical record analysis and the use of risk assessment tools, thereby prioritising the need for ergonomic intervention. In particular, the effects of varying restricted and overhead work heights on the biomechanical, physiological and psychophysical responses of an individual were investigated. Twenty-eight subjects were required to complete sixteen conditions. The conditions consisted of the adoption of restricted and upright overhead static postures, with half requiring the holding of four kilograms of weight in the hands and the remaining eight conditions having no weight. Testing was carried out using an electromyography unit, ergospirometer and a perceptual Body Discomfort Map and Scale. This involved a habituation and testing session. The results of the testing revealed the biomechanical and physiological responses were dependant on the change in height. Body discomfort was also shown to be variable over the changing height conditions. This indicates that there is a significant effect of height on an individual's responses during overhead work. The extreme restricted (-200mm and -100mm) and upright (+300mm and +400mm) overhead conditions within this study were limiting, as they elicited the highest muscle activation, physiological responses and body discomfort ratings. Positions that are preferable to adopt, which were identified from the results in this study, indicate conditions closer to head height (0mm and +100mm) were favourable. The results therefore illustrate how awkward working postures during work are likely to elicit higher demands from an individual, which could lead to an increased risk for the development of a musculoskeletal disorder. The added factor of weight elicited significant results over all variables, excluding a respiratory The focus of this investigation was an analysis of the work demands being placed on South African automotive industry workers as there is a recognised problem with regard to the prevalence of musculoskeletal disorders (MSDs). Preliminary work was conducted to highlight the dominant risks and areas which elicited higher numbers of MSDs within the chosen automotive plant. An area of concern was highlighted through medical record analysis and the use of risk assessment tools, thereby prioritising the need for ergonomic intervention. In particular, the effects of varying restricted and overhead work heights on the biomechanical, physiological and psychophysical responses of an individual were investigated. Twenty-eight subjects were required to complete sixteen conditions. The conditions consisted of the adoption of restricted and upright overhead static postures, with half requiring the holding of four kilograms of weight in the hands and the remaining eight conditions having no weight. Testing was carried out using an electromyography unit, ergospirometer and a perceptual Body Discomfort Map and Scale. This involved a habituation and testing session. The results of the testing revealed the biomechanical and physiological responses were dependant on the change in height. Body discomfort was also shown to be variable over the changing height conditions. This indicates that there is a significant effect of height on an individual's responses during overhead work. The extreme restricted (-200mm and -100mm) and upright (+300mm and +400mm) overhead conditions within this study were limiting, as they elicited the highest muscle activation, physiological responses and body discomfort ratings. Positions that are preferable to adopt, which were identified from the results in this study, indicate conditions closer to head height (0mm and +100mm) were favourable. The results therefore illustrate how awkward working postures during work are likely to elicit higher demands from an individual, which could lead to an increased risk for the development of a musculoskeletal disorder. The added factor of weight elicited significant results over all variables, excluding a respiratory individual.
Keywords: Human engineering -- South Africa; Industrial safety -- South Africa; Automobile industry workers -- South Africa -- Health risk assessment; Automobile industry and trade -- South Africa -- Safety measures; Musculoskeletal system -- Wounds and injuries -- Prevention; Lifting and carrying -- Safety measures; Work measurement; Posture